A model of transient internal flow and atomization of propellant/ethanol mixtures in pressurized metered dose inhalers (pMDI). Issue 5 (4th May 2018) - Gavtash, B.; Versteeg, H. K.; Hargrave, G.; Myatt, B.; Lewis, D.; Church, T.; Brambilla, G.
ABSTRACT: This article reports the extension to binary propellant/excipient mixtures of the multiphase model of transient internal flow and atomization in pressurized metered dose inhalers (pMDIs) of Gavtash and colleagues for propellant-only flows. The work considers different accounts of the effect of less volatile ethanol on the saturated vapor pressure (SVP), viscosity and surface tension of HFA-based pMDI formulations. Representation of the SVP of HFA/ethanol mixtures by Raoult's law is compared with the empirical model developed by Gavtash and colleagues as well as different theoretical mixing rules for surface tension and viscosity. For initial ethanol contents ranging from 0 to 20% by mass, the temperature, pressure and spray velocity were predicted to be almost independent of ethanol concentration when using the empirical SVP model of Gavtash and colleagues. The predicted aerosol droplet size increases with increasing concentration of ethanol. These model predictions compare favorably with phase Doppler anemometry (PDA) measurements of pMDI sprays. Exploration of model predictions with different mixing rules suggest that variations of the dynamic viscosity could result in 0.7 µm droplet size change, and different surface tension models yield around 1.5 µm droplet size change. The findings of this work challenge the view that the increase of droplet size is caused by the low volatility of excipients such as ethanol. Instead, attention is focused on composition-dependent viscosity and surface tension as potential controlling parameters with significant effect on the droplet size of HFA/ethanol sprays. Copyright © 2018 American Association for Aerosol Research